Localization of the neuropeptides pituitary adenylate cyclase-activating polypeptide, vasoactive intestinal peptide, and their receptors in the basal brain blood vessels and trigeminal ganglion of the mouse CNS; an immunohistochemical study - Anne Marie Lund; Anne Marie Lund; Jens Hannibal; Jens Hannibal (Frontiers Media S.A., 2022)
Pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) are structurally related neuropeptides that are widely expressed in vertebrate tissues. The two neuropeptides are pleiotropic and have been associated with migraine pathology. Three PACAP and VIP receptors have been described: PAC1, VPAC1, and VPAC2. The localization of these receptors in relation to VIP and PACAP in migraine-relevant structures has not previously been shown in mice. In the present study, we used fluorescence immunohistochemistry, well-characterized antibodies, confocal microscopy, and three-dimensional reconstruction to visualize the distribution of PACAP, VIP, and their receptors in the basal blood vessels (circle of Willis), trigeminal ganglion, and brain stem spinal trigeminal nucleus (SP5) of the mouse CNS. We demonstrated a dense network of circularly oriented VIP fibers on the basal blood vessels. PACAP nerve fibers were fewer in numbers compared to VIP fibers and ran along the long axis of the blood vessels, colocalized with calcitonin gene-related peptide (CGRP). The nerve fibers expressing CGRP are believed to be sensorial, with neuronal somas localized in the trigeminal ganglion and PACAP was found in a subpopulation of these CGRP-neurons. Immunostaining of the receptors revealed that only the VPAC1 receptor was present in the basal blood vessels, localized on the surface cell membrane of vascular smooth muscle cells and innervated by VIP fibers. No staining was seen for the PAC1, VPAC1, or VPAC2 receptor in the trigeminal ganglion. However, distinct PAC1 immunoreactivity was found in neurons innervated by PACAP nerve terminals located in the spinal trigeminal nucleus. These findings indicate that the effect of VIP is mediated via the VPAC1 receptor in the basal arteries. The role of PACAP in cerebral arteries is less clear. The localization of PACAP in a subpopulation of CGRP-expressing neurons in the trigeminal ganglion points toward a primary sensory function although a dendritic release cannot be excluded which could stimulate the VPAC1 receptor or the PAC1 and VPAC2 receptors on immune cells in the meninges, initiating neurogenic inflammation relevant for migraine pathology.